PENYULUHAN HUKUM MEREK KOLEKTIF BAGI UMKM ROTE NDAO: PENINGKATAN PEMAHAMAN DAN KESIAPAN PENDAFTARAN BERDASARKAN UNDANG-UNDANG NOMOR 20 TAHUN 2016 TENTANG MEREK DAN INDIKASI GEOGRAFIS - Yossie Maria Yulianty Jacob; Chatryen M Dju Bire; Orpa Juliana Nubatonis; Juliana S Ndolu; Melinda Ratu Radja; Rini M Kaesmetan; Daud Yaferson Dollu (Universitas Mataram, 2026)
Intellectual property, particularly trademarks, is legally protected under national law. Collective trademarks serve as an important instrument for empowering Micro, Small, and Medium Enterprises (MSMEs). They offer benefits such as cost efficiency and enhanced regional reputation, making them an effective tool for local development. Rote Ndao Regency has various high-potential local products, including seaweed-based processed goods. Protecting these products through a Collective Trademark is essential to preserve their authenticity and increase their competitiveness in the market. This activity was conducted with the Seaweed Business Group “Setia Usaha” in Oelolot Village, West Rote District, Rote Ndao Regency, on 28 August 2025, with 25 participants in attendance. The program aimed to provide legal counseling on the protection and registration procedures of Collective Trademarks for the community of Rote Ndao, in order to safeguard and enhance the competitiveness of local products. The method used in this program was legal dissemination delivered through lectures and interactive discussions. This approach was chosen to ensure effective knowledge transfer and to allow participants to raise specific questions related to the potential of their local products. The activity successfully increased participants’ understanding of the urgency and benefits of Collective Trademarks, including cost efficiency and their role in preserving the identity and quality of local products. Participants also gained a clearer understanding of the requirements and procedures for registering a Collective Trademark. This improved awareness is expected to encourage MSME actors and community groups to proceed with Collective Trademark registration, thereby obtaining legal protection and strengthening the competitive value of Rote Ndao’s leading products. Overall, the legal counseling effectively enhanced the community’s understanding of Collective Trademarks, marking an important first step toward protecting and advancing their local products.